The pyrin inflammasome, a leading actor in pediatric autoinflammatory diseases - La Bella, Saverio; Di Ludovico, Armando; Di Donato, Giulia; Basaran, Ozge; Ozen, Seza; Gattorno, Marco; Chiarelli, Francesco; Breda, Luciana (Frontiers in Immunology, 2024)
The activation of the pyrin inflammasome represents a highly intriguing mechanism employed by the innate immune system to effectively counteract pathogenic agents. Despite its key role in innate immunity, pyrin has also garnered significant attention due to its association with a range of autoinflammatory diseases (AIDs) including familial Mediterranean fever caused by disruption of the MEFV gene, or in other genes involved in its complex regulation mechanisms. Pyrin activation is strictly dependent on homeostasis-altering molecular processes, mostly consisting of the disruption of the small Ras Homolog Family Member A (RhoA) GTPases by pathogen toxins. The downstream pathways are regulated by the phosphorylation of specific pyrin residues by the kinases PKN1/2 and the binding of the chaperone 14-3-3. Furthermore, a key role in pyrin activation is played by the cytoskeleton and gasdermin D, which is responsible for membrane pores in the context of pyroptosis. In addition, recent evidence has highlighted the role of steroid hormone catabolites and alarmins S100A8/A9 and S100A12 in pyrin-dependent inflammation. The aim of this article is to offer a comprehensive overview of the most recent evidence on the pyrin inflammasome and its molecular pathways to better understand the pathogenesis behind the significant group of pyrin-related AIDs.